ASSESSMENT OF EXAM QUESTIONS QUALITY ACCORDING TO COGNITIVE DOMAIN OF BLOOM’S TAXONOMY - Merisa Kartikasari; Tri Atmojo Kusmayadi; Budi Usodo (Proceedings Education and Language International Conference, 2017)
2013 curriculum specially prepared students to compete in a global education. Therefore, it provided students an exam with Higher Order Thinking questions. In the learning process, the questions would play a central role. The aim of this research is to describe cognitive domain of midle school semester 1 exam questions composed by the teacher. This research is qualitative-descriptive research. The subjects were two teachers in Senior High School 1 Cawas. One teacher was a senior subject and the other was a beginner subject. The techniques of collecting data was documentation. The data were validated using triangulation method. All data were analyzed using the model of Miles and Huberman. The result on the study showed that the most common middle school semester 1 exam questions used by all subjects were application aspect whereas analysis aspect was least used. Even, in beginner subjects, analysis aspect was not used at all. The quality of both questions arranged by the two subject was different. Question arranged by senior subject could not be resolved directly. Students had to interpret the questions to other form. Even, the question arranged by beginner subject could be resolved directly without interpreting the intent question first. Questions of comprehension aspect arranged by senior subject demanded skills of students to change the question to other form. Even in beginner subject, questions could be solved simply by applying the formula. Question of analysis aspect was only used by senior subject. In this aspect, question was around of conclusion of logarithm.Keywords: Bloom’s Taxonomy, Cognitive Domain, Mathematics Teacher